The World Bank annual report 2008 : (World Bank, 2008)
Poverty estimates in this report use international poverty lines that are based on 1993 purchasing power party (PPP) conversion factors. This was the latest measure of press time. The content of the report is about: the message form the President of WB and Chairman of the Board of Excecutive Directors; WB group fiscal year highlights; inclusive and sustainable globalization; regional perspctives and summary of fiscal year activity.